The Widow's Strike - Taylor, Brad 1965- (New York Penguin, 2014)
When a rogue state plots to unleash a genetically mutated virus, the Taskforce counter terrorism unit under Pike Logan and Jennifer Cahill follows a dangerous trail across Southeast Asia to the United States.
Keywords: Special forces (Military science) -- United States; Fiction; Special operations (Military science) -- Fiction; Suspense fiction; Thrillers (Fiction)